Firm Size Moderation in Digital Environmental Disclosure, Online Attention, and Stock Prices - Suryopratomo, Anggit; Majidah, Majidah; Mahaputra, M. Syafaruddin; Widuri, Awat; Fujiana, Dara (International Journal of Economics Development Research (IJEDR), 2025)
The objective of this study is to investigate the effect of digital environmental disclosure and online attention on stock prices, and the moderating role of company size in non-cyclical consumer goods issuers on the Indonesia Stock Exchange. The Green Digital Marketing Intensity (GDMI) index represents digital environmental disclosure and is constructed from green communication traces on corporate websites and official social media. Online attention is measured using a composite index derived from Google search interest and corporate website traffic. Grounded in signaling theory, legitimacy theory, stakeholder theory, and the attention-based view, the study positions GDMI and online attention as signals that influence market assessment, while company size acts as a structural factor that alters signal strength. A balanced panel of 14 issuers during 2021–2024 (56 firm-year observations) was analyzed using Feasible Generalized Least Squares panel regression under inter-firm heteroscedasticity. The results show that GDMI, online attention, and company size positively and significantly affect stock price logs. However, the interaction between GDMI and size is negative and significant, while the interaction between ATT and size is positive and significant. These indicate that digital environmental disclosure has a stronger effect on stock prices in smaller companies, whereas online attention has a larger effect in bigger companies. In conclusion, digital green communication footprints and online attention are valued by the market, yet their influence depends on firm size. Practically, digital green communication strategies should be tailored to company scale, and future research is encouraged to expand sectors, periods, and digital attention indicators. Keywords: Digital environmental disclosure; Firm size; GDMI; Online attention; Stock prices.